Study the Proportion Prevalence of Cytomegalovirus, Robella Virus, and Herpes Simplex Virus to Aborted Women in Iraq through the Period from 2021A.D. to 2023A.D - Gihad, Zeena Kareem; Ghazal, Sabreen G. (American Journal of Biology and Natural Sciences, 2025)
The study aims to investigate Rubella, cytomegalovirus [CMV], and herpes simplex virus [HSV] in aborted women and find the proportion prevalence of infections with these viral causes. To achieve this goal, 963 Blood samples were taken from all participants for screening for this viral infection. The samples were collected from different hospitals and outside labs in Iraq, through the period [from 4 January 2021 A.D. to 20 December 2023 A.D.]. A cross-sectional and analytical study [for the TORCH test] was conducted on pregnant women [age ≥20 and ≤41 years] with miscarriage history. The result of the current study illustrated the distribution of aborted women according to the age of viral infections, the highest frequency was in the age group [31-35 years] [28%] and the lowest frequency was in the age group [≤41 years] [7%]. The study also shows the distribution of aborted women according to the proportion of viral infection. The highest frequency was in CMV [50%] and the lowest frequency was in Rubella [34%], and HSV [27%] respectively. The distribution of aborted women according to several abortions shows the highest frequency was in one abortion [50%] and the lowest frequency was in three or more abortions [23%]. Also, the present study shows the distribution of aborted women according to viral infections in the pregenual period. The first trimester had the highest frequency of HSV [41%] and the lowest frequency was in other infections [34%]. The distribution of aborted women in the second trimester showed that the highest frequency was in HSV [33%] and the lowest frequency was Rubella [27%]. Also, in the third trimester was the highest frequency in other infections [36%] and the lowest frequency was in HSV [26%]. The study showed the distribution of aborted women according to viral infections through three years ago. In 2021 A.D. the highest frequency was in CMV [38%] and the lowest frequency was in other infections [31%]. While the distribution of aborted women in 2022 A.D. the highest frequency was in other infections [43%] and the lowest frequency was in CMV [32%]. Also, in 2023 A.D. the highest frequency was in Rubella [34%] and the lowest frequency was in in other infections [26%].